Pengaruh Konsentrasi GulaTerhadap Karakteristik Kimia dan Organoleptik Wine Durian (Durio zybethinus Murr) - Pardjala, Gaspar; Moniharapon, Erynola; Tuhumury, Helen C D; Hamza, Wahyuningsih (Universitas Pattimura, 2024)
Fruit Wine is an alcoholic drink that is usually made from fermented fruits. This research aims to determine the appropriate sugar concentration to obtain durian wine's best chemical and organoleptic characteristics. This research uses RAL with one factor: sugar concentration with three concentration treatment levels: KG1 = 10%, KG2 = 20%, and KG3 = 30%. The research results on wine treated with a sugar concentration of 30% is the right concentration to produce durian wine with good characteristics and acceptable chemical and organoleptic characteristics. Durian wine with a sugar concentration of 30% has an alcohol content of 10.6%, total sugar of 13.84, and pH of 4.45. Durian wine added sugar, which is 30% preferred for taste, color, aroma, and overall likeness.